Allelic Polymorphism of enos Gene in Children Who Suffer from Bronchial Asthma, with Eosinophilic and Paucigranulocytic Subtypes of Bronchial Inflammation - L.O. Bezrukov; O.K. Koloskova; T.M. Bilous; N.K. Bohutska (Zaslavsky O.Yu., 2015)
The objective of the research was to study the effect of allelic polymorphism of eNOS gene, encoding the activity of endothelial NO-synthase and synthesis of nitrogen monoxide in the airways, on some clinical and paraclinical parameters of bronchial asthma in school-age children with eosinophilic and paucigranulocytic inflammatory subtypes. We have examined 22 patients with bronchial asthma with eosinophilic nature of the airway inflammation and 15 patients - with paucigranulocytic one. The immunological, spirometric studies, genotyping of endothelial NOS were carried out. The severity of bronchial asthma in patients with different types of bronchial inflammation doesn't depend on allelic polymorphism of the eNOS gene. The absence ofeNOS gene mutations as GG genotype was characteristic of patients with paucigranulocytic bronchial inflammation, allelic polymorphism GT/TT - of children with eosinophilic inflammation. In the presence of allelic polymorphism of eNOS gene as  GT/TT genotype, children with paucigranulocytic bronchial inflammation were characterized by more frequent clinical manifestations of atopic dermatitis and allergic rhinitis, higher bronchial lability index and lower concentrations of NO metabolites in the exhaled breath condensate.